Serum uric acid levels as a risk stratification tool in hypertensive pregnancy - Saldanha, Cimona Lyn; Malik, Sabha; Quraishi, Azhar Un-Nisa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hypertensive disorders represent the most common medical complication of pregnancy affecting between 7-15% of all gestations and accounts for approximately a quarter of antenatal admissions. Methods: A case-control study was conducted over a period of 1 year. A total of 200 subjects were enrolled in the study and were divided into two groups; 100 cases and 100 controls. Serum uric acid levels were measured in cases and controls. The serum uric acid levels were correlated with the severity of PIH and maternal and fetal complications. Results: It was observed that the mean serum uric acid level in cases (5.0±1.74 mg/dl) was significantly higher compared to 2.66±0.39 mg/dl in controls. Serum uric acid levels also tended to increase with increasing severity of PIH, increasing from 3.69±0.95 mg/dl in gestational hypertension to 6.36±1.38mg/dl in severe PE. Maternal complications during antepartum and postpartum period were higher once SUA≥5mg/dl was taken as a cut-off. Protienuria(p=0.00), coagulopathy(p=0.007), need for blood/platelet transfusion(p=0.01) and eclampsia (p= 0.007) were significantly more. Similarly, complications were found to be higher, in babies born to mothers having serum uric acid more than 5 mg/dl compared to others in case group. Conclusions: Higher serum uric acid levels may indicate higher risk of progression to preeclampsia and development of adverse maternal/infant conditions.